Searching for Drug Synergy Against Cancer Through Polyamine Metabolism Impairment: Insight Into the Metabolic Effect of Indomethacin on Lung Cancer Cells - López-Contreras, Freddy; Muñoz-Uribe, Matías; Pérez-Laines, Jorge; Ascencio-Leal, Laura; Rivera-Dictter, Andrés; Martin-Martin, Antonia; Burgos, Rafael A.; Alarcon, Pablo; López-Muñoz, Rodrigo (Frontiers in Pharmacology, 2020)
Non-small cell lung cancer (NSCLC) is the most lethal and prevalent type of lung cancer. In almost all types of cancer, the levels of polyamines (putrescine, spermidine, and spermine) are increased, playing a pivotal role in tumor proliferation. Indomethacin, a non-steroidal anti-inflammatory drug, increases the abundance of an enzyme termed spermidine/spermine-N1-acetyltransferase (SSAT) encoded by the SAT1 gene. This enzyme is a key player in the export of polyamines from the cell. The aim of this study was to compare the effect of indomethacin on two NSCLC cell lines, and their combinatory potential with polyamine-inhibitor drugs in NSCLC cell lines. A549 and H1299 NSCLC cells were exposed to indomethacin and evaluations included SAT1 expression, SSAT levels, and the metabolic status of cells. Moreover, the difference in polyamine synthesis enzymes among these cell lines as well as the synergistic effect of indomethacin and chemical inhibitors of the polyamine pathway enzymes on cell viability were investigated. Indomethacin increased the expression of SAT1 and levels of SSAT in both cell lines. In A549 cells, it significantly reduced the levels of putrescine and spermidine. However, in H1299 cells, the impact of treatment on the polyamine pathway was insignificant. Also, the metabolic features upstream of the polyamine pathway (i.e., ornithine and methionine) were increased. In A549 cells, the increase of ornithine correlated with the increase of several metabolites involved in the urea cycle. Evaluation of the levels of the polyamine synthesis enzymes showed that ornithine decarboxylase is increased in A549 cells, whereas S-adenosylmethionine-decarboxylase and polyamine oxidase are increased in H1299 cells. This observation correlated with relative resistance to polyamine synthesis inhibitors difluoromethylornithine and SAM486 (inhibitors of ornithine decarboxylase and S-adenosyl-L-methionine decarboxylase, respectively), and MDL72527 (inhibitor of polyamine oxidase and spermine oxidase). Finally, indomethacin demonstrated a synergistic effect with MDL72527 in A549 cells and SAM486 in H1299 cells. Collectively, these results indicate that indomethacin alters polyamine metabolism in NSCLC cells and enhances the effect of polyamine synthesis inhibitors, such as MDL72527 or SAM486. However, this effect varies depending on the basal metabolic fingerprint of each type of cancer cell.